2016
DOI: 10.1038/labinvest.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

ResolvinD1 reduces apoptosis and inflammation in primary human alveolar epithelial type 2 cells

Abstract: 1Lung epithelial apoptosis and inflammatory responses are important pathological processes in many pulmonary disorders. ResolvinD1 (RvD1), generated in inflammatory resolution processes, reduces inflammatory responses in animal models of lung diseases. The aim of this study was to investigate whether RvD1 attenuates apoptosis and proinflammatory responses in primary human alveolar epithelial type 2 cells (AEC2 cells) that are exposed to lipopolysaccharide (LPS) in vitro. We examined the percentage of apoptotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Inappropriate or massive stimulation of autophagy can actually facilitate cell death. Our previous work showed that apoptotic pulmonary cells also plays a critical role during the process of ALI [44]. In addition, MV or CS-induced autophagy and apoptosis in fetal rat lung epithelial cells [45], suggesting that such autophagic cell death exhibits an essential role in MV or CS model.…”
Section: Discussionmentioning
confidence: 95%
“…Inappropriate or massive stimulation of autophagy can actually facilitate cell death. Our previous work showed that apoptotic pulmonary cells also plays a critical role during the process of ALI [44]. In addition, MV or CS-induced autophagy and apoptosis in fetal rat lung epithelial cells [45], suggesting that such autophagic cell death exhibits an essential role in MV or CS model.…”
Section: Discussionmentioning
confidence: 95%
“…Proresolving lipid mediators, including lipoxins, resolvins, protectins, and maresins, are syn-thesized from omega-3 fatty acids (eicosapentaenoic acid and docosahexaenoic acid) and omega-6 fatty acids (arachidonic acid) (5,24). RvD1 is a kind of resolvin that displays dramatic inflammation-proresolving activities (35,36). FPR2/ALX is a G protein-coupled receptor with multiple binding partners, including the endogenous lipid mediators RvD1, lipoxin A4, and the Ca 2ϩ -dependent phospholipid-binding protein annexin A1.…”
Section: Discussionmentioning
confidence: 99%
“…However, LXA4 restored the function of the epithelial barriers by reversing the inhibition of LPS on AT II cell proliferation and reducing apoptosis of AT II cells induced by LPS. In addition, LXA4 promoted primary AT II cell proliferation and reduced apoptosis induced by LPS [25, 26].…”
Section: Discussionmentioning
confidence: 99%